Pentingnya Rencana dalam Sebuah Pemerintahan - Habibatul Qalbi; Tarisha Lingke Lubis; Ghassani Marisah Hasibuan (Lembaga Pengembangan Kinerja Dosen, 2024)
Plans are a vital component in a government to achieve directed and sustainable development. This research aims to identify the importance of plans in managing resources, setting priorities, and creating transparency and accountability in government. The method used in this research is qualitative analysis based on literature reviews and case studies related to plan implementation in various governments, both national and local. The focus of this research includes the role of plans in resource efficiency, risk mitigation, and coordination between institutions. The research results show that governments that have thorough planning are better able to optimize the use of budget, labor and time compared to governments without clear plans. In addition, a good plan helps the government anticipate potential risks and challenges, as well as provide strategic solutions to face them. In terms of transparency, planning documents enable the public to monitor government performance, increase public trust, and support public participation in the development process. This research also found that plans that are inclusive and involve various stakeholders are able to create stronger synergy between institutions and maintain program sustainability even if there is a change in leadership. In conclusion, plans in government are not only a tool to direct development, but also an important instrument to ensure stability, effectiveness and efficiency. With a structured plan, the government can achieve development goals optimally and have a significant impact on community welfare. This research recommends strengthening planning capacity at all levels of government to improve the quality of governance and public services.